Neutrophilic dermatoses in a seronegative rheumatoid arthritis patient: A case report - Amel Awad IbnIdris Rodwan; Abdel Gaffar. A. Mohammed; Mohammed Elmujtba Adam Essa; Atif Elhadi Abdalla Babker; Ali Mohamed Abdelsatir; Elnour Mohammed Elagib (Clinical Case Reports, 2022)
Abstract Rheumatoid arthritis (RA) is a chronic inflammatory disease, characterized by symmetric and destructive polyarthritis with a broad‐spectrum clinical manifestation of various organs. RND is an unusual distinctive manifestation of RA and typically develops in severe RA. This report aims to present an unusual and a rare neutrophilic skin condition, in a seronegative RA Sudanese patient. A 51‐year‐old woman was diagnosed with RA three years ago and a history of bilateral polyarthritis, presented with a skin rash involving her extremities and abdomen. Clinical examination of her skin revealed the presence of maculopapular lesions affecting the extensor surfaces of the lower extremities and the lower part of the abdomen with hyperpigmentation. Hand X‐ray demonstrated periarticular osteopenia, and laboratory and immunological studies that include C‐reactive protein, erythrocyte sedimentation rate (ESR), rheumatoid factor (RF), anticitrullinated peptide antibodies (ACPAs), and antinuclear factor in addition to skin biopsy were all suggested a diagnosis of neutrophilic dermatosis. The patient received steroids for the skin lesion still no significant improvement was seen, and then, cyclosporin 100 mg was administrated twice/ day with close monitoring, and two weeks later marked improvement was shown.